PERANCANGAN STRATEGI PEMASARAN UMKM LUMINTU DENGAN PENDEKATAN METODE SWOT DAN METODE QUANTITATIVE STRATEGIC PLANNING MATRIX (QSPM) - Ahmad Maulana; Amalia Maghfiroh; Ardana Farahdiansari (Universitas Muhammadiyah Gresik, 2023)
Lumintu is one of the SMEs engaged in the production of 'balung kuwuk' and banana chips. In marketing its products, Lumintu faces a challenge of unstable sales. This research utilizes the SWOT Matrix IFE-EFE and Quantitative Strategic Planning Matrix (QSPM) methods. The IFE-EFE matrices are used to identify the Internal and External factors that influence the product sales in Lumintu SME. The purpose of the IFE and EFE matrices is to determine the ranking value and weight of each internal and external factor. The analysis is then continued using the Quantitative Strategic Planning Matrix (QSPM). The result of the methods used indicates that the marketing strategy for 'balung kuwuk' and banana chips products falls into quadrant 4, which represents the 'Grow and Build' strategy. This quadrant is derived from the total score of IFE matrix weight (3.11) and the total score of EFE matrix weight (2.93).